Effect of Nano- And Microparticles on Germination and Development of Tomato Plants (Eurasian Research Bulletin, 2022)
The article contains information on the application of generite (Co, Cu, Zn, Mn), silicon dioxide (SiO2), manganese dioxide (MnO2) and iron oxide (Fe2O3) nano and microparticles to tomato crops, as well as the effects of these particles and their compositions on the germination of tomato seeds the results of the experiment conducted in order to study the effect on the yield and the development of its seedlings are presented. Before planting tomato seeds, silicon dioxide (SiO2), manganese dioxide (MnO2) and iron oxide (Fe2O3) 1 g each and silicon dioxide (SiO2)+manganese dioxide (MnO2)+iron oxide (Fe2O3)-1,5 g An effective effect on fertility was observed. If manganese dioxide (MnO2) and iron oxide (Fe2O3) are added to tomato seedlings grown from tomato seeds at the rate of 1 gram per 10 liters of water, a positive effect on the development of the plant was found. It was observed that 10% and 75% flowering was 6-7 days earlier in the variants using silicon (SiO2), manganese (MnO2) and iron (Fe2O3) oxides. In turn, it was found that fruiting in these variants was 9-10 days earlier (10%) compared to the control, and at the same time, it was observed that the obtained yield was significantly higher